Edukasi Gizi dan Pelatihan Pembuatan Makanan Kaya Nutrisi dan Probiotik Menggunakan Labu Kuning - Qumiyatul Lailiyah, Binti; Sandera, Deli; Fiki Masyaroti, Nabilah; Ansori, Miksan (LP3M IAIFA Kediri, 2024)
This research is research carried out in the context of carrying out the tridharma of higher education at the Faqih Asy'ari Islamic Institute of Religion (IAIFA) Kediri. This type of research is Community Service Research (PKM). The implementation of this research was carried out objectively and the researchers took part in providing assistance. The purpose of this research is to provide counseling and assistance to accelerate the reduction of stunting in Sukoharjo Village through Nutrition Education and Training on Making food rich in nutrients and probiotics to prevent stunting in children. The method to be used in this research is the PAR or Participatory Action Research method. Participatory Action Research is a research model that looks for something to link the research process into the process of social change. The social change in question is how the empowerment process can realize three benchmarks, namely increasing the accessibility of health services for everyone, increasing public understanding of the importance of balanced nutrition for optimal growth of children, involving joint activities from local communities in efforts to prevent stunting through participatory posprogramm in posyandu. Stages in this study: 1. Researchers will make observations to determine the point of existing problems/analysis of the community situation. 2. Problem identification. 3. Define specific work goals. 4. Problem solving plan. 5. Social approach. 6. Implementation of counseling and training activities. 7. Establishment of extension pilots 8. Evaluation and results activities. After this research is over, it is hoped that this research can be published in the form of journals or book chapters and books.